Reply to Taheripour, Delgado and Tyner (2020). (April 2020) - Santeramo, Fabio Gaetano; Searle, Stephanie
Abstract: The present letter is aimed at providing a step-by-step comment on the criticisms raised by Taheripour, Delgado and Tyner, authors of the Response to Santeramo and Searle (2019). The paper by Santeramo and Searle (2019) analyses the responsiveness of the US soy and palm oil markets to price changes. The authors find positive cross-price elasticities of palm oil import with respect to soy oil price, and vice versa. Hereafter we will refer to the paper by Taheripour, Delgado and Tyner as TDT (2020) and to the paper by Santeramo and Searle as SS (2019).